The Changing Face of Maritime Power
XI, 198 p.
Keywords: The end of the Cold War has affected debates about maritime strategy, doctrine, operations and technology. What has emerged is an intellectual reconsideration of the theory and practise of maritime power. This volume addresses these themes in a systematic and over-arching way, and brings together contributions from internationally renowned scholars. It focuses on the implications for western navies of shifts in strategic thinking, maritime doctrine, technology and naval roles.